The Role of Social Media in Strengthening or Weakening Democracy in Indonesia - Adinda Farrah Dwi Citra; Dzaky Muhammad Dzakir Damanik; Kinan Shofia Aimy; Rida Syafiyyah; Taqiyan Azzarah Warits Al Haqq (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Social media causes several problems in the democratic process. These include the spread of misinformation, political polarization, and the spread of hate speech. The purpose of this study is to analyze the positive and negative impacts of social media on public participation in the digital era and the democratic process. The data collection technique used in this study was a literature review method, analyzing written sources and selecting those relevant to the three main topics of social media, globalization, and democracy. The sources were reviewed and explained in narrative form. The results of the study indicate that social media has a significant influence on democracy. Social media plays a positive role as a means for people to channel their aspirations, provide criticism, and provide suggestions. Social media also has negative impacts such as the spread of fake news and hate speech.